1984
DOI: 10.1902/jop.1984.55.12.679
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Root Planing and Citric Acid Applications on Flap Healing in Humans: A Histologic Evaluation

Abstract: Four human teeth and their facial gingival attachment were removed en block 3 months after periodontal flap therapy and citric acid root conditioning and then prepared for histologic evaluation. At the time of periodontal surgery, and prior to citric acid application, the facial root surface was grooved at midline and citric acid was applied only to one-half of each root surface. Tissues were decalcified and histologically prepared as horizontally oriented, step serial sections from the level of the gingival m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…A novel approach to treat root surfaces altered by the disease process has been the use of demineralization. It has been shown that healing of the non-diseased root surfaces begins with dentin demineralization, followed by cementogenesis and regeneration of the attachment apparatus.78 However, clinical data supporting the use of citric acid have been equivocal.23 28 Currently, the success of regenerative periodontal procedures which utilize citric acid demineralization can best be regarded as "unpredictable." The use of tetracycline, on the other hand, is gaining much interest among clinicians, due to its collagenase-inhibiting potential in addition to its acidic and antimicrobial properties.…”
Section: Discussionmentioning
confidence: 99%
“…A novel approach to treat root surfaces altered by the disease process has been the use of demineralization. It has been shown that healing of the non-diseased root surfaces begins with dentin demineralization, followed by cementogenesis and regeneration of the attachment apparatus.78 However, clinical data supporting the use of citric acid have been equivocal.23 28 Currently, the success of regenerative periodontal procedures which utilize citric acid demineralization can best be regarded as "unpredictable." The use of tetracycline, on the other hand, is gaining much interest among clinicians, due to its collagenase-inhibiting potential in addition to its acidic and antimicrobial properties.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our department reported on closure by epithelial adhesion following root demineralization in human suprabony lesions without evidence of new attachment (Stahl & Froum 1977, Kashani et al 1984. Con- Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the unsuccessful periodontal repairs after citric acid treatment (Stahl & Froum 1977, Renvert & Egelberg 1981. Albair et al 1982. Kashani et al 1984.…”
Section: Effects Of Citric Acid Treatmentmentioning
confidence: 99%
“…This in turn induces the development of a connective tissue attachment to the denuded root (Postlethwaite et al, 1978, Gauss-Muller et al, 1980. Glynn 1981, Poison & Proye 1982, Hanes et al, 1985, Wikesjo et al, 1991, However, several authors, some on clinical grounds, others in comparison with a control group, have described weak or equivocal results after citric acid application (Stahl et al, 1983, Gottlow et al, 1984, Kashani et al 1984, Ibbot et al, 1985, Kersten et al, 1992, Thus, in search of optimal clinical results, the techniques for root surface acid conditioning were most often studied in vitro with particular attention paid to parameters such as the pH of the acid solution (Register & Burdick 1975, Hennequin et al, 1994, the duration and mode of its application (Sterett & Bain 1987, Sterett & Murphy 1989m, Labahn et al, 1992, Wen et al, 1992, the effectiveness of the scaling and/or root planing techniques (Rabbam et al, 1981, Cafesse et al, 1986, Breininger et al 1987, Fleischer et al, 1989, Eschler & Rapley 1991, and the quality of the residual root surfaces (Blomlof et al, 1987(Blomlof et al, , 1989,…”
mentioning
confidence: 99%